Florida's Water Resources - Roy R. Carriker; Tatiana Borisova (EDIS)
FE757, a 9-page illustrated fact sheet by Roy R. Carriker and Tatiana Borisova, provides an overview of Florida’s water resources organized with reference to the hydrologic cycle. Includes references. Published by the UF Department of Food and Resource Economics, December 2008.